2014
DOI: 10.1007/978-1-4939-1785-3_16
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Stem Cells in the Adult Mammalian Ovary

Abstract: Female mammals are born with a fixed pool of germ cells, which does not replenish during adult life. However, this has been recently challenged and adult ovaries produce oocytes throughout adult life just like sperm in the testes. Evidence is accumulating on the presence of ovarian stem cells, but the need for robust protocols to isolate, identify, further characterize, and subject them to various functionality tests is essential. Knowledge about the function and potential of ovarian stem cells is well demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 31 publications
4
35
0
Order By: Relevance
“…They have described in a very lucid manner how the research progressed in the field and we thank them for confirming by flow cytometry that indeed DDX-1 positive ovarian stem cells (OSCs) co-express OCT-4. This confirms that the stem cells isolated from ovarian cortical tissue by Tilly’s group by flow cytometry [ 2 ] are similar to the OCT-4 positive stem cells isolated by mechanical scraping of ovary surface epithelium (OSE) by our group [ 3 , 4 ]. This type of third party confirmation and validation of presence of stem cells in adult mammalian ovary is necessary to convince the scientific community and bring about a paradigm shift in the field of ovarian biology.…”
Section: Commentarysupporting
confidence: 82%
See 1 more Smart Citation
“…They have described in a very lucid manner how the research progressed in the field and we thank them for confirming by flow cytometry that indeed DDX-1 positive ovarian stem cells (OSCs) co-express OCT-4. This confirms that the stem cells isolated from ovarian cortical tissue by Tilly’s group by flow cytometry [ 2 ] are similar to the OCT-4 positive stem cells isolated by mechanical scraping of ovary surface epithelium (OSE) by our group [ 3 , 4 ]. This type of third party confirmation and validation of presence of stem cells in adult mammalian ovary is necessary to convince the scientific community and bring about a paradigm shift in the field of ovarian biology.…”
Section: Commentarysupporting
confidence: 82%
“…But we have shown the co-existence of two distinct populations of stem cells in OSE including the ovary germ stem cells (OGSCs) which are the same as OSCs and a small sub-population of very small embryonic-like stem cells (VSELs) [ 3 , 4 ]. The basic difference between the two populations is their size and OCT-4 expression (Fig.…”
Section: Commentarymentioning
confidence: 99%
“…4 In human ovaries, MSC have been found to play a role in the mesenchymal-epithelial transition of ovarian tunica albuginea. 5,6 It was suggested that multipotent or pluripotent cells might be present in ovarian tissue. 5,7 Nonetheless, even though the ovary constantly undergoes substantial tissue remodelling, limited studies have focused on the presence of mesenchymal stem cells in the mammalian ovary.…”
Section: Introductionmentioning
confidence: 99%
“…The mesenchymal stem cell population in the OSE are called ovarian stem cells (OSCs). OSCs are larger in size and committed to differentiating into primordial follicles [10,14]. Research groups are going into individual avenues on how GCs, VSELs and OSCs could potentially be used in clinical applications.…”
Section: Introductionmentioning
confidence: 99%